The Family Resilience in Preventing Domestic Violence Cases - Wulandari, Retno; Andaryuni, Lilik (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
Marriage is a contract, namely a handover between the guardian of a female candidate and a male candidate, this handover and acceptance is a form of responsibility for one goal. Early marriage is a marriage carried out by couples who are considered teenagers, namely those under 19 years of age. It will be difficult for women to report incidents of domestic violence that happen to them for several reasons, personal, family, and even cultural reasons surrounding the victim of domestic violence. Therefore, maintaining family integrity can avoid factors that cause divorce, one of which is domestic violence. The researchers used qualitative research methods with library methods and data collection techniques using secondary source data to help strengthen this research. Therefore, how can families maintain family ties to build a sakinah mawaddah warahmah family, and then also look for solutions and solutions to solve domestic violence problems so that undesirable things do not happen. This research helps to determine how families can build family resilience and provide solutions, and also helps families to avoid factors that cause divorce in the family